Lateral facial profile of β-thalassemia major in Javanese children: a photogrammetric analysis - Parengkuan, Wulan Geraldine; Kuswandari, Sri; Soeprihati, Indah Titien (Medical Journal of Indonesia, 2023)
BACKGROUND Impairment of globin chain synthesis in patients with β-thalassemia major causes ineffective erythropoiesis. This condition triggers bone marrow hyperplasia and can lead to craniofacial bone abnormalities. This study aimed to evaluate the lateral facial profile of β-thalassemia major, identify any differences when compared with a control group of similar age and ethnicity, and reveal the facial profile of β-thalassemia major in Javanese children. METHODS This cross-sectional study included 35 β-thalassemia major children aged 7–15 years. They were divided into 3 groups based on their age. Lateral facial photogrammetry was taken by measuring the forehead protrusion and nasolabial angle. Data were then mapped to the normal group of children in the same age group and descriptively analyzed using SPSS software. RESULTS The 1 and 2 SD group had a higher prevalence of β-thalassemia major in children aged 7–9 years for both sexes. The older age group had a closer mean value to those of children without thalassemia. CONCLUSIONS The forehead and maxillary profile of Javanese β-thalassemia major children tended to be protrusive, especially in the 7–9 years age group, while the older age groups had closer mean values to those of children without thalassemia.